Work-related experiences of prostate cancer survivors in Australia: a qualitative study - Liu, Wei-Hong; Fox, Jennifer; Yates, Patsy (BMC public health, 2023)
Background Prostate cancer (PCa) is the most diagnosed cancer in Australian men, and the number of survivors is growing with advances in diagnosis and treatment. Work participation following PCa diagnosis and treatment becomes a significant aspect of quality of life and survivorship. Using a qualitative phenomenological approach, we explored the work-related experiences of PCa survivors in Australia. Methods Semi-structured telephone interviews were conducted with 16 men (6 salaried employees, 10 self-employed; 8 diagnosed ≥ 5 years) purposively sampled from a community setting. Interviews were inductively analysed. Results Five main themes emerged: motivations to work; treatment decisions and work; the effects of PCa and its treatment on ability to participate in work; being an employee versus being self-employed; and personal agency. PCa and its treatment side-effects were detrimental to men’s work capacity and ability, and could persist over an extended period. Most men expressed a strong desire to retain work or return to work. Discussions with healthcare professionals about work-related consequences were largely missing when treatment decisions were made. Self-employed men faced greater challenges than their salaried counterparts due to high financial burden and limited social and business support. Family, workplace and wider community support, and self-care, enhanced men’s work participation experiences. Conclusions PCa and its treatment substantially and persistently impacted men’s working lives, and their experiences were diverse and multifaceted. Self-employed and long-term PCa survivors face greater challenges and are at high risk of poor work outcomes. A systematic approach and involvement of stakeholders at all levels is required to support ongoing work participation.